Enhancing Teaching and Learning through Assessment Deriving an Appropriate Model - Frankland, Steve (Springer Netherlands : Imprint: Springer, 2007)
Assessment is the daily life of a teacher; designing plans, setting questions, giving feedback and grading are all activities that teachers undertake on a regular basis. Yet, the close examination of such activities can be hindered by constraints caused by the context in which different teaching and learning activities occur and an unawareness of the effect that assessment has on the students themselves. This book provides a practical guide on the effective use of assessment. It includes the use of assessment tools and pedagogical design that help students deepen their learning. Major issues on assessment and some excellent examples are presented as a useful resource to university teachers in enhancing teaching and students' learning. It will also be found useful by teachers when implementing various assessment methods. School administrators and teaching development professionals will find the book useful when making decisions related to learning and teaching issues in their institutions.